2011
DOI: 10.1038/cddis.2011.19
|View full text |Cite
|
Sign up to set email alerts
|

PERP expression stabilizes active p53 via modulation of p53-MDM2 interaction in uveal melanoma cells

Abstract: The activation and regulation of target genes by the tumour-suppressor p53 dictates the fate of a cell, with cell cycle arrest or apoptosis being two distinct outcomes. PERP (p53 apoptosis effector related to PMP-22), a p53 transcriptional target, is induced specifically during apoptosis but not cell cycle arrest. Downregulation of PERP is associated with the aggressive, monosomy 3-type of uveal melanoma (UM), the most common primary intraocular tumour in adults, and increased PERP expression has a pro-apoptot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 37 publications
(80 reference statements)
3
37
0
Order By: Relevance
“…PERP was previously identified as a p53 target gene by subtractive cloning of mouse embryonic fibroblasts and was shown to be expressed exclusively in apoptotic cells. 30 Interestingly, PERP can feed back to p53 to promote its activity 41 which is consistent with our observation that PERP and p53 cooperate to promote apoptosis in ECs. Our findings also resonate with previous studies that revealed post-translational modifications of p53 playing a role in disturbed flow-mediated EC apoptosis and contributing to atherosclerotic plaque formation.…”
Section: Discussionsupporting
confidence: 83%
“…PERP was previously identified as a p53 target gene by subtractive cloning of mouse embryonic fibroblasts and was shown to be expressed exclusively in apoptotic cells. 30 Interestingly, PERP can feed back to p53 to promote its activity 41 which is consistent with our observation that PERP and p53 cooperate to promote apoptosis in ECs. Our findings also resonate with previous studies that revealed post-translational modifications of p53 playing a role in disturbed flow-mediated EC apoptosis and contributing to atherosclerotic plaque formation.…”
Section: Discussionsupporting
confidence: 83%
“…147,148 The regulation of p53 protein half-life is crucial to his function 149,150 and, consequently, for cancer progression. [151][152][153] This proteosomal degradation is indeed a powerful therapeutic target. [154][155][156][157][158] The full-length p53 tetramer, bound to DNA, acquires different quaternary conformations 82 where the C-terminal and DBD directly interact; the N-terminal seems to only weakly associate with DBD, and no direct interactions between N-terminal and C-terminal are observed.…”
Section: Discussionmentioning
confidence: 99%
“…As such an important regulator, the control of p53 protein status becomes crucial for cancer progression [15,16]. However, the question of how p53 defines which programs of cell cycle arrest, DNA repair pathways, or apoptosis to initiate is still debatable.…”
Section: Introductionmentioning
confidence: 99%